Analysis of regulating ecosystem services at the mediterranean nature reserve of Castelporziano (Rome, Italy) in response to changing environmental conditions - G. Scarascia-Mugnozza; F. Manes; A. Sebastiani; S. Fares (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)
The Castelporziano Presidential Estate, a State Nature Reserve of roughly 6,000 hectares covered by natural forests, with over 30 years of field data collection is a precious data hub that might contribute to better understand the effects of Climate Change abiotic and biotic-related stress on natural vegetation and, eventually, to their ecosystem services provision. This research presents on-going studies on plant-environment interactions conducted within the Estate, with a focus on ecosystem carbon fluxes, pollution (ozone and particulate matter), drought and heat stress, and biotic infections that have occurred over time. The present study concentrates over the period from 2013 to 2024. In the first part, we present a series of continuous measurements on a semi-hourly basis, which was undertaken to build up a time series capable of interpreting the effect of the control factors (climate, ecological processes, water availability) on the eco-physiological parameters of the holm oak forest. Ten years of high-frequency measurements allowed us to estimate the possible effect of climate and water availability on carbon assimilation. The holm oak forest of Castelporziano showed high rates of carbon assimilation each year with minimal changes in response to drought and high temperatures, thus making this ecosystem particularly resilient to climate changes. In the second part, we present remote sensing-based analyses that investigate changes of vegetation health and function over the last six years, which were affected by both biotic (pest invasion) and abiotic (more frequent and intense droughts) factors.

Zinc acetate concentration-dependent ammonia gas sensing properties of ZnO sensors - Jagruti S. Mane; Pritamkumar V. Shinde; Gitanjali F. Jadhav; Tariq Mslih Saad Ahmed; Bhagwat N. Pawar; Suhas S. Mohite; Rajaram S. Mane (Next Research, 2025)

Mn and S-doped nickel molybdate/nickel molybdate hydrate micro-structures for supercapacitor applications - Ahmed H. Al-Naggar; Vijaykumar V. Jadhav; Shoyebmohamad F. Shaikh; Balaji G. Ghule; Rajaram S. Mane (Chemical Engineering Journal, 2025)

Projected impacts of climate change on ecosystem services provided by terrestrial mammals in Brazil - Luara Tourinho; Stella Manes; Aliny P.F. Pires; João Carlos Nabout; José Alexandre F. Diniz-Filho; Levi Carina Terribile; Marinez Ferreira de Siqueira; Geiziane Tessarolo; Maria Lúcia Lorini; Marcio Argollo de Menezes; Danilo Boscolo; Mariana M. Vale (Ecosystem Services, 2025)

Nature-based solutions potential for flood risk reduction under extreme rainfall events - Stella Manes; Mariana M. Vale; Aliny P. F. Pires (Ambio, 2024)

Modelling PM10 removal in three Italian coastal Metropolitan Cities along a latitudinal gradient - L. Nardella; A. Sebastiani; M. Stafoggia; P.P. Franzese; F. Manes (Ecological Modelling, 2023)

Effects of dust and meteorological variables on temperature inversion over Kuwait - Mariam Malek; Ali Al-Hemoud; Manar AlSaraf; Mohammed F. Yassin; Ahmad Al-Khayat; Mane Al-Sudairawi (Modeling Earth Systems and Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The effectiveness of climate action and land recovery across ecosystems, climatic zones and scales - Stella Manes; Mariana M. Vale; Aliny P. F. Pires (Regional Environmental Change, 2022)

Implementation of IUCN criteria for the definition of the Red List of Ecosystems in Italy - G. Capotorti; L. Zavattero; R. Copiz; E. Del Vico; L. Facioni; S. Bonacquisti; R. Frondoni; M. Allegrezza; F. Attorre; G. Bacchetta; E. Barni; E. Biondi; et al. (Plant Biosystems, 2020)

More nature in the city - G Capotorti; S Bonacquisti; L Abis; I Aloisi; F Attorre; G Bacaro; G Balletto; E Banfi; E Barni; F Bartoli; E Bazzato; M Beccaccioli; et al. (Plant Biosystems, 2020)

Effects of nitrogen deposition, drought and their interaction, on functional and structural traits of Fraxinus ornus L. and Quercus ilex L. - L. Fusaro; E. Salvatori; F. Manes (Plant Biosystems, 2016)

A multiscale analysis of canopy structure in Fagus sylvatica L. and Quercus cerris L. old‐growth forests in the Cilento and Vallo di Diano National Park - F. Manes; C. Ricotta; E. Salvatori; S. Bajocco; C. Blasi (Plant Biosystems, 2010)

Magnetic Basement Depth Inversion in the Space Domain - Tiago Mane Nunes; Valéria Cristina F. Barbosa; João Batista C. Silva (Pure and Applied Geophysics, 2008)

Monitoring tropospheric ozone impact on plants in natural and urban areas with a Mediterranean climate - F. Manes; M. Vitale; M. Di Traglia (Plant Biosystems, 2005)

Root plasticity in Mediterranean herbaceous species - M. De Lillis; F. Manes; F. Tufaro (Plant Biosystems, 2005)

Impaired set-shifting and dissociable effects on tests of spatial working memory following the dopamine D2 receptor antagonist sulpiride in human volunteers - Mitul A. Mehta; Facundo F. Manes; Gianna Magnolfi; Barbara J. Sahakian; Trevor W. Robbins (Psychopharmacology, 2004)

Morpho-functional characteristics of Quercus ilex L. leaves of different age and their ecophysiological behaviour during different seasons - F. MANES; G. ASTORINO; M. VITALE; F. LORETO (Plant Biosystems, 1997)